A test of ear preference for music - SU, Nandur (Journal of All India Institute of Speech and Hearing)
Based on a pilot study, a test was developed with 13 events out of which 10 were test events and 3 were control events. In each test event one ear gets a constan piece of tune and the other ear receives the distorted version of th1e constant tune and two other distorted tunes, one at a time in a dichotic fashion." After listening to the whole event, the subject was asked to find out as to which one of the three distorted tunes resembles the constant piece of tune in the other ear. In a control event, the distorted version of the constant tune was not present and it was replaced by another distorted tune. The subject was expected to indtcate that there was no resemblance between the constant and the three distorted tunes.